2022
DOI: 10.3390/cells11223641
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor (ICI) Genes and Aging in Clear Cell Renal Cell Carcinoma (ccRCC): Clinical and Genomic Study

Abstract: Background: It is anticipated that there will be a large rise in the number of tumor diagnoses and mortality in those aged 65 and older over the course of upcoming decades. Immune checkpoint inhibitors, often known as ICIs, boost immune system activity by selectively targeting ICI genes. On the other hand, old age may be connected with unfavorable results. Methods: The Cancer Genome Atlas (TCGA) provided gene expression data from ccRCC tissue and key clinical variables. ICI gene databases were applied and veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…For patients who had routine clear cell mRCC surgery, Sorbellini and colleagues developed a postoperative prognostic nomogram to aid the prediction of recurrence in patients with mRCC ( Kattan et al, 2001 ; Sorbellini et al, 2005 ; Zhang et al, 2018 ). In the treatment modalities, chemotherapy and surgery used as a monotherapy in mRCC improve survival relative to non-use, whereas, there is no change in radiation treatment, and that could be due to the significant impact of newly discovered targeted treatments in recent years ( Al-Danakh et al, 2022 ). In the study of chemotherapy and surgery usage, better survival significance were connected to therapeutic applications of both chemotherapy and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who had routine clear cell mRCC surgery, Sorbellini and colleagues developed a postoperative prognostic nomogram to aid the prediction of recurrence in patients with mRCC ( Kattan et al, 2001 ; Sorbellini et al, 2005 ; Zhang et al, 2018 ). In the treatment modalities, chemotherapy and surgery used as a monotherapy in mRCC improve survival relative to non-use, whereas, there is no change in radiation treatment, and that could be due to the significant impact of newly discovered targeted treatments in recent years ( Al-Danakh et al, 2022 ). In the study of chemotherapy and surgery usage, better survival significance were connected to therapeutic applications of both chemotherapy and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer immunity cycle consists of seven steps from the release of tumor antigen to the lysis of tumor cells which requires the participation of immune system [ 83 ]. Most importantly, ICIs such as PD-1/PD-L1 and CTLA-4 inhibitors play a central role in the treatment of mRCC [ 84 , 85 ]. Immune evasion can occur at the steps of antigen presentation and activation, transportation of T cells and tumor infiltration and cytotoxic activity of T cells in TME; it can lead to primary or adaptive resistance in patients receiving immunotherapy [ 86 , 87 ].…”
Section: Biological Rationale For Combined Icis and Targeted Therapymentioning
confidence: 99%
“…Finally, among the most altered genes in cancer with age are those of the immune microenvironment, which plays an important role in cancer prognosis and therapy. Hence, identifying and validating immune-related biomarkers associated with aging in cancer holds immense potential for clinical applications ( Figure 3 ) ( 19 , 28 , 58 , 59 ).…”
Section: Immune-related Genes and Agingmentioning
confidence: 99%
“…Further, TNFSF15 may simultaneously decrease the expression of VEGFR1 on the cell membrane and increase the synthesis of soluble VEGFR1, shifting the VEGF/VEGFR1 signaling pathway from promoting angiogenesis to inhibiting angiogenesis ( 200 ). Our team previously revealed that TNFSF15 gene expression was downregulated in clear cell renal cell carcinoma of geriatric with negative association between the TNFSF15 gene expression and age ( 59 ). Moreover, the protein-protein interaction between TNFSF15, other immune checkpoints, and proteins associated with aging demonstrates TNFSF15’s involvement in the aging mechanism.…”
Section: Immune-related Genes and Agingmentioning
confidence: 99%